2016
DOI: 10.1589/jpts.28.3078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthotic insoles on adults with flexible flatfoot under different walking conditions

Abstract: [Purpose] This study was to evaluate the effects of orthotics on adults with flexible flatfoot when wearing orthotic insoles while walking on horizontal ground, walking up and down stairs and to determine if flexible flatfoot needs treatment. [Subjects and Methods] Fifteen college students with flexible flatfoot and fifteen college students with normal feet were recruited. First, load rate and contact area were measured by RSscan force plate when the subjects were walking on horizontal ground, walking up and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In fact, some studies on children have shown no difference between treated and untreated subjects, strengthening the hypothesis that the improvements documented in other studies were more likely the result of the physiological spontaneous development of the longitudinal arch rather than of medical treatments. 34 , 35 Additionally, even if some authors have documented beneficial effects of insoles 36 and foot exercises, 37 a few recent systematic reviews have concluded that there is little evidence in favour of orthotics, bracing and stretching exercises for children 13 and of orthotics for adults. 38 Therefore, only in cases of severe non-operable forms of flatfoot should customised orthopaedic footwear be prescribed.…”
Section: Flatfootmentioning
confidence: 99%
“…In fact, some studies on children have shown no difference between treated and untreated subjects, strengthening the hypothesis that the improvements documented in other studies were more likely the result of the physiological spontaneous development of the longitudinal arch rather than of medical treatments. 34 , 35 Additionally, even if some authors have documented beneficial effects of insoles 36 and foot exercises, 37 a few recent systematic reviews have concluded that there is little evidence in favour of orthotics, bracing and stretching exercises for children 13 and of orthotics for adults. 38 Therefore, only in cases of severe non-operable forms of flatfoot should customised orthopaedic footwear be prescribed.…”
Section: Flatfootmentioning
confidence: 99%
“…Present-day insoles utilise solid filling underneath the foot arch to support and/or correct the arch shape in order to reduce pain and related symptoms such as plantar fasciitis and knee osteoarthritis. [7][8][9] However, it is reported that such support results in elevated stress of foot joints and ligaments. 10 Moreover, it restricts the MLA dynamic response and compromises the natural MLA action during gait.…”
Section: Introductionmentioning
confidence: 99%
“…This information guides clinicians to make decisions for orthotic therapy to improve foot mechanics and relieve pain [3]. Many studies have been performed on the use of foot orthoses [4][5][6][7], insoles [8][9][10][11], UCBL shoe inserts [12,13] and supra-mallolar orthoses [14] for flat feet. The efficacy of these orthoses was evaluated primarily in terms of pain reduction, gait and foot (talo-calcaneal and tarso-metatarsal) angle measurements.…”
Section: Introductionmentioning
confidence: 99%